NADPH Oxidase 5 (NOX5) Upregulates MMP-10 Production and Cell Migration in Human Endothelial Cells - Javier Marqués; Elena Ainzúa; Josune Orbe; María Martínez-Azcona; José Martínez-González; Guillermo Zalba (MDPI AG, 2024)
NADPH oxidases (NOXs) have been described as critical players in vascular remodeling, a mechanism modulated by matrix metalloproteinases. In this study, we describe for the first time the upregulation of MMP-10 through the activation of NOX5 in endothelial cells. In a chronic NOX5 overexpression model in human endothelial cells, MMP-10 production was measured at different levels: extracellular secretion, gene expression (mRNA and protein levels), and promoter activity. Effects on cell migration were quantified using wound healing assays. NOX5 overexpression increased MMP-10 production, favoring cell migration. In fact, NOX5 and MMP-10 silencing prevented this promigratory effect. We showed that NOX5-mediated MMP-10 upregulation involves the redox-sensitive JNK/AP-1 signaling pathway. All these NOX5-dependent effects were enhanced by angiotensin II (Ang II). Interestingly, MMP-10 protein levels were found to be increased in the hearts of NOX5-expressing mice. In conclusion, we described that NOX5-generated ROS may modulate the MMP-10 expression in endothelial cells, which leads to endothelial cell migration and may play a key role in vascular remodeling.